The Correlation Between Total Cholesterol and Blood Glucose Levels with Physical Activity in Construction Workers - Tri Prasetyorini; Neiny Prisy Foekh; Angki Purwanti; Anissa Salsabilla Yuliana; Annisya Widiyanti Atmaja (jitek, 2026)
Coronary heart disease (CHD) and Diabetes Mellitus (DM) are non-communicable diseases (NCDs), caused by elevation of total cholesterol and blood glucose levels. Both indicators can be influenced by physical activity, determined by the type of work people do. Construction workers’ jobs involve a lot of physical activity with moderate to heavy intensity. This study aims to determine the correlation between total cholesterol and blood glucose levels with physical activity among construction workers. Employing an analytical observational design with a cross-sectional approach, the research involved 32 construction workers from Jatiwarna without a history of CHD and DM, who fasted before undergoing total cholesterol and blood glucose tests. The Global Physical Activity Questionnaire (GPAQ) was utilized to measure physical activity. The collected data were analyzed statistically and revealed that construction workers most frequently engage in heavy physical activity, with 25 individuals (78.1%) participating. The total cholesterol level ranged from 98.3 to 269.62 mg/dL, with mostly normal levels, but 10 participants (31.3%) had high total cholesterol levels. In terms of fasting glucose levels, the value ranged from 45.17 to 114.24 mg/dL, mostly normal except for 15 participants (53.1%) with abnormal levels. Spearman's correlation test showed a correlation between physical activity and total cholesterol levels (p-value of 0.003), as well as a correlation between physical activity and fasting glucose levels (p-value of 0.001). In conclusion, physical activity affects total cholesterol and blood glucose levels, which require balanced consideration alongside nutritious intake to maintain optimal metabolism.